PHYSICAL EDUCATION IN THE CONTEXT OF SPECIAL EDUCATION: STRATEGIES, CHALLENGES AND TEACHING ACHIEVEMENTS (REMUNOM, 2025)
This study analyzed the strategies, challenges, and achievements of Physical Education teachers who work with students with disabilities in the context of inclusive education. The qualitative, descriptive-exploratory research was conducted through a structured questionnaire administered to teachers at a gym affiliated with a sports club in the municipality of Poços de Caldas, southern Minas Gerais. Seven teachers participated in the study, and their responses were analyzed in light of the relevant scientific literature. The results showed that, although many teachers began their careers with enthusiasm and enthusiasm, they also reported feelings of insecurity due to a lack of specific training and a lack of institutional support. Even so, they demonstrated resilience and commitment to finding adapted methodologies and pedagogical practices that met the needs of students with disabilities. Ongoing training proved essential for transforming teaching practices, while strategies such as dialogue with families, the use of alternative materials, and collaborative activities were highlighted as facilitators of the inclusion process. The reported achievements point to progress in student engagement, stronger self-esteem, and improved athletic and educational performance. The research concludes that investment in public policies that ensure ongoing training, adequate infrastructure, and technical and pedagogical support for teachers is essential, fostering the consolidation of a truly inclusive Physical Education system. Despite the challenges faced, the teachers demonstrated commitment, confidence, and initiative, envisioning the expansion of their inclusive practices through ongoing training, scientific events, the creation and implementation of projects in the field, and interdisciplinary partnerships.